Separable asymptotic cost of evaluating elementary functions - Favati, P.; Lotti, G.; Menchi, O.; Romani, F. (Numerical algorithms, 2000)
The computational cost, in the bit model of computation, of the evaluation of a real function in a point is analyzed, when the number d of correct digits of the result increases asymptotically. We want to study how the cost depends on also when approaches a critical point for the function f. We investigate the hypotheses under which it is possible to give upper bounds on the cost as functions of “separated variables” d and , that is as products of two functions, each of one variable. We examine in particular the case of elementary functions.